2017
DOI: 10.4103/0253-7176.198947
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Associated Factors among Diabetic Patients at Mekelle City, North Ethiopia

Abstract: Background:Coexistence of mental health problems on diabetes mellitus can result in poor management of the illness, poor adherence to treatment, and low quality of life. Therefore, it is highly crucial to assess these problems; thus we carried out this study with the aim of determining the prevalence of depression and identifying related factors among diabetic patients at city of Mekelle, North Ethiopia.Methods:Hospital-based cross-sectional study was employed among 264 diabetic patients, and participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
13
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
9
13
3
1
Order By: Relevance
“…The finding of our study that one-fifth of patients with T2DM (18%) suffered from major depression is similar to the findings of a systematic review by Roy and Lloyd where the they found a prevalence of 19.1% (range 6.5–33%) [ 4 ] however the finding is considerably higher compared to that of a collaborative study carried out in 14 countries which found a prevalence of 10.6% [ 38 ]. The rate of major depression in this study is also comparable to rates of depression in studies from Nigeria with a prevalence of 19.4% based on the SCID [ 39 ] and from Ethiopia with a prevalence of 17% on the Beck Depression Inventory (BDI) [ 40 ].…”
Section: Discussionsupporting
confidence: 79%
“…The finding of our study that one-fifth of patients with T2DM (18%) suffered from major depression is similar to the findings of a systematic review by Roy and Lloyd where the they found a prevalence of 19.1% (range 6.5–33%) [ 4 ] however the finding is considerably higher compared to that of a collaborative study carried out in 14 countries which found a prevalence of 10.6% [ 38 ]. The rate of major depression in this study is also comparable to rates of depression in studies from Nigeria with a prevalence of 19.4% based on the SCID [ 39 ] and from Ethiopia with a prevalence of 17% on the Beck Depression Inventory (BDI) [ 40 ].…”
Section: Discussionsupporting
confidence: 79%
“…The nding of our study that one-fth of patients with T2DM (18%) suffered from major depression is similar to the ndings of a systematic review by Roy and Lloyd where the they found a prevalence of 19.1% (range 6.5-33%) (4) however the nding is considerably higher compared to that of a collaborative study carried out in 14 countries which found a prevalence of 10.6% (34). The rate of major depression in this study is also comparable to rates of depression in studies from Nigeria with a prevalence of 19.4% based on the SCID (35) and from Ethiopia with a prevalence of 17 % on the Beck Depression Inventory (BDI) (36).…”
Section: Discussioncontrasting
confidence: 42%
“…The nding of our study that one-fth of patients with T2DM (18%) suffered from major depression is similar to the ndings of a systematic review by Roy and Lloyd where the they found a prevalence of 19.1% (range 6.5-33%) (4) however the nding is considerably higher compared to that of a collaborative study carried out in 14 countries which found a prevalence of 10.6% (34). The rate of major depression in this study is also comparable to rates of depression in studies from Nigeria with a prevalence of 19.4% based on the SCID (35) and from Ethiopia with a prevalence of 17 % on the Beck Depression Inventory (BDI) (36).…”
Section: Discussionsupporting
confidence: 78%